Oral health related quality of life and disease severity in autoimmune bullous diseases - (:unkn) unknown (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2020)
Background: There is an increased risk of long-term dental and periodontal disease in autoimmune bullous diseases (AIBD). Aims: In this cross-sectional study, we aimed to determine whether the oral health-related quality of life status (OHRQoL) was associated with disease severity and activity in patients with AIBD. Subjects and Methods: 67 patients with AIBD were enrolled in this study. Autoimmune Bullous Skin Disorder Intensity Score (ABSIS) was used to evaluate the disease severity. The score was categorized as a significant course (>= 17) and moderate course (<17). Oral health impact profile-14 (OHIP-14) questionnaire was filled to assess the OHRQoL. Self-reported oral health status and oral lesion related pain score were also evaluated in the study group. Results: OHIP-14 score was significantly higher in active patients (42.28 +/- 13.66) than inactive patients (29.08 +/- 12.25) (P = 0.004) and it was correlated with the pain score (6.33 +/- 2.78; r = 0.409, P = 0.013). Furthermore, OHIP-14 score was higher in patients with a significant disease course (45.18 +/- 15.08) (P = 0.010) than in patients with a moderate course (36.09 +/- 9.73). Conclusions: OHRQoL may be useful in the disease management and treatment. Since it can be affected by both presence of oral erosions and disease severity, a collaboration between dermatologists and dentists could be crucial to the disease management in AIBD.
Keywords: Autoimmune bullous diseases; bullous pemphigoid; health related quality of life; oral health; pemphigus vulgaris; CENTERED OUTCOME MEASURES; INTENSITY SCORE ABSIS; PEMPHIGUS-VULGARIS; PERIODONTAL STATUS; TRIAMCINOLONE ACETONIDE; BEHCETS-DISEASE; MUCOSAL DISEASE; LICHEN-PLANUS; IMPACT; RELIABILITY